REVITALISASI KAMPUNG CINA DI KOTA BENGKULU (2016-2022) - Yuniarti, Indah Tri; Erniwati, Erniwati (Ensiklopedia of Journal, 2024)
Abstract: This article discusses the revitalisation of Kampung Cina in Bengkulu City (2016-2022) with a focus on the background, stages, and impacts of the revitalisation carried out by the government. The revitalisation of Kampung Cina was motivated by the government's awareness of the potential of Kampung Cina as a cultural and historical tourism destination and to welcome the Visit 2020 Wonderful Bengkulu program. The programme aims to increase tourist visits to Bengkulu because although Bengkulu's tourist attractions are many, the number of tourists who come is relatively small. The reason why this research is important is because the topic of research on Kampung Cina in Bengkulu city has not been studied in depth, even though the historical and cultural values contained can add to science. This research uses the historical method which has four steps, namely heuristics, source criticism, interpretation, and historiography. The main sources used are documents and interviews. The results of this study show that the government has several policies for Kampung Cina in Bengkulu. The revitalisation of Kampung Cina is divided into several stages namely; 1) physical revitalisation in the form of making sidewalks, installing street lights, and painting buildings. 2) economic rehabilitation, the government held a bazaar to improve the economy of the Kota Tuo community. 3) socialisation, the government communicated the revitalisation to the community. The revitalisation of Kampung Cina has a good impact on the economic, social, and tourism sectors despite the constraints of Covid-19. Keywords: Kampung Cina, Revitalization, Visit 2020 Wonderful Bengkulu, Bengkulu Tourism